1989
DOI: 10.1524/zkri.1989.187.14.253
|View full text |Cite
|
Sign up to set email alerts
|

Neutron powder diffraction study of a Na,Cs-Rho zeolite

Abstract: Zeoüte Rho / Aluminosilicate framework distortion / Variation of pore size / Neutron powder diffraction / (Si, Al)-0 bond lengthsAbstract. The crystal structure of a Na, Cs-Rho zeolite was studied at 373 Κ (Na8.4Cs3.2Si36.4Aln.6O96 · 5D 2 0) by neutron powder diffraction and Rietveld profile analysis. It crystallizes in the noncentrosymmetric space group /43m and has a unit cell constant a = 14.6566(4) Â. The final residuals are R¡ = 9.65% and R wp = 8.01%. The distortion of the (Al,Si)0 2 -framework of this z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This value is slightly larger than the one reported by Baur Δ = 1.57 Å. 26 According to Corbin et al 19 , the degree of distortion is related to the charge density of the cations located within the D8R windows. In this work, for NaCs-RHO(H2O) the occupancy factor of the Cs + cations sitting in the center of the D8R window site is larger than the one reported by Baur in agreement with a lower Si/Al ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This value is slightly larger than the one reported by Baur Δ = 1.57 Å. 26 According to Corbin et al 19 , the degree of distortion is related to the charge density of the cations located within the D8R windows. In this work, for NaCs-RHO(H2O) the occupancy factor of the Cs + cations sitting in the center of the D8R window site is larger than the one reported by Baur in agreement with a lower Si/Al ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…In this work, for NaCs-RHO(H2O) the occupancy factor of the Cs + cations sitting in the center of the D8R window site is larger than the one reported by Baur in agreement with a lower Si/Al ratio. 26 These extra-framework charge-compensating cations influence the distortion of the D8Rs, which is similar to the effect of temperature, ion-exchange or adsorption of different molecules in RHO-type zeolites. On the other hand, it has been shown that the high water content of the NaCs-RHO(H2O) sample is due to the higher Si/Al ratio which can also influence the RHO framework, i.e.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The third effect is known in previously studied cases of framework deformation in dehydrated zeolitic frameworks. [18][19][20][21] We describe here an investigation of structural changes in dehydrated Sr-ETS-4. Powder neutron diffraction data from heat-treated Sr-ETS-4 samples have been analyzed by the Rietveld method to determine the structures of Sr-ETS-4 heattreated at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, zeolite RHO (Figure 1) undergoes framework distortions upon alteration in the type of extraframework cation and degree of hydration. 5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] This unusual flexibility has been extensively investigated for aluminosilicate compositions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We recently reported the synthesis and characterization of an aluminogermanate with the zeolite RHO topology 27,28 that possesses a framework Ge/ Al ratio of unity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] This unusual flexibility has been extensively investigated for aluminosilicate compositions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We recently reported the synthesis and characterization of an aluminogermanate with the zeolite RHO topology 27,28 that possesses a framework Ge/ Al ratio of unity. This contrasts with aluminosilicate rho which tends to have Si/Al ∼ 3, 8,29,30 but is more similar to the gallosilicate which has Si/Ga ∼ 1.3.…”
Section: Introductionmentioning
confidence: 99%